Pain Treatment among Underserved Older Adult African Americans - Yazdanshenas, Hamed (J Am Geriatr Soc, 2016)
Older adult African Americans who experience pain are especially at high-risk for under assessment and treatment. This study examined the patterns and correlates of pain medication use that include the following: severity of pain, medical conditions, and access to care. Four hundred African American older adults aged 65 years and older were recruited from 16 churches located in South Los Angeles. Structured face-to-face interviews and visual inspection of each participant’s medications were conducted. More than 39% of participants were 75 years and older and 65% were female. Forty-seven percent used at least one type of pain medication. The frequency of pain medication use by pharmaceutical class was as follows: non-opioid (33%), opioid (12%), adjuvant (9%), and other drug (8%). Furthermore, 77% of non-opioids were Non-Steroidal Anti-Inflammatory Drugs (NSAIDs) and were used among 25%, 28%, 26%, and 28% of participants with hypertension, stroke, kidney disease, and gastrointestinal problems, respectively. Among participants who used NSAIDs, 98%, 69%, and 65% experienced Potentially Inappropriate Medication (PIM) use, drug duplication, and drug-drug interactions, correspondingly. This study suggests a severe mismanagement of pain among underserved African American older adults, particularly among individuals with co-morbidity, multiple providers, and limited access to health care. The use of pain medication was associated with drug-drug interactions, drug duplication, and PIM use. Our data shows that a large number of participants with severe pain are either not taking pain medication or experience PIM use. One out of four participants was taking NSAID pain relievers, which can cause serious side effects among aged African Americans with multiple chronic conditions.